PENGEMBANGAN GAME EDUKASI â€œLINGED MATHâ€ PADA MATERI LINGKARAN SMP - Nurbuono, Mousthapaa; Kristiana, Arika Indah; Hussen, Saddam; Wihardjo, Edy; Murtikusuma, Randi Pratama (Universitas Muhammadiyah Ponorogo, 2024)
Educational games are games specifically designed with educational themes to get learning outcomes. This research develops an educational game